Tailoring resistive switching properties of TiO2 with controlled incorporation of oxide nanoparticles. (19th August 2016) - Rios, Alejandro Cristians; Aarão-Rodrigues, Lorena; Cadore, Alisson Ronieri; de Andrade, Rodrigo R; Montoro, Luciano A; Malachias, Angelo
Abstract: Reversible resistance states were extensively observed in thin film systems, and their physical properties were in most cases determined by the electric behavior of the dielectric layer placed between contacts. Here we include SnO2 nanoparticles on TiO2 dielectric films, inducing modifications of the resistive switching behavior. We show that the choice of oxide nanoparticles with dielectric constant smaller than the dielectric constant of the main oxide film guides conductive channels, increasing the extension of the Fowler–Nordheim (tunneling) conduction regime during their electroforming as the density of nanoparticles rises. It is found that the SnO2 nanoparticles show reduced impact on the resistive switching response of devices produced following this methodology. The formation of Ti4 O7 conductive channels is discussed based on electric measurements as well as on scanning probe and electron microscopy techniques.